Quantitative Substitution of Raw Baobab (Adansonia digitata) Seed Meal for Soyabean Meal in Broiler Starter Diet - Saulawa , L.A.; Ukachukwu, S.N.; Onwudike, O.C.; Garba, M.G.; Aruwayo, A. (International Journal of Poultry Science, 2014)
A 28-day feeding trial involving 150 day old Anak broiler chicks was carried out to study the effect of quantitative substitution of raw baobab (Adansonia digitata) seed meal (RBSM) for soyabeans meal in broiler starter diet. The birds were grouped into five dietary treatments of 0, 5, 10, 15 and 20 levels of inclusion of Raw Baobab Seed Meal (RBSM), in a completely randomized design. Feed and water were offered to birds ad libitum. Result of productive performance shows significant differences (p